The German Socio-Economic Panel (SOEP) in the Nineties: An Example of Incremental Innovations in an Ongoing Longitudinal Study - Gert G. Wagner (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
The main aim of the present paper is to historically reappraise the development of the German Socio-Economic Panel Study (SOEP) in the 1990s after the first six waves had been collected. This development was closely connected to the opening of the Iron Curtain in Eastern Europe and the fall of the Wall separating the two German states. In addition to its relevance for the SOEP, this study is also of interest in relation to the contemporary history of science.
Keywords: B23; C89; Y50; 330; SOEP; German unification; immigration studies; research governance; survey methods